Bipolar Lumbar Radiofrequency Medial Branch Neurotomy in a Patient with Deep Brain Stimulation Implant - Bara, Gregor A.; Salemdawod, Abdallah; Vychopen, Martin; Rana, Shaleen; Vatter, Hartmut; Maciaczyk, Jaroslaw; Scorzin, Jasmin; Banat, Mohammed (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2022)
Chronic axial lower back pain is one of the most common conditions that patients seek medical attention for in pain practices. About 15 to 40% of axial lower back pain is due to facet-mediated pain. Diagnostic blocks of the medial branch reliably identify the facet joint as the pain generator and offer a prognostic factor for response to radiofrequency neurotomy of the identified facet joints resulting in profound pain relief. However, deep brain stimulation implants have been considered a contraindication for neurotomy. We present an illustrative case of a patient with deep brain stimulation system treated with bipolar medial branch neurotomy using a two-needle technique.
Keywords: chronic neuropathic back and leg pain; spinal surgery; deep brain stimulation; thermal radiofrequency ablation